Negative electrode for lithium secondary battery and method for producing same

By adopting a two-layer negative electrode active layer in a lithium secondary battery and combining magnetic field processing technology to adjust the structure of carbon-based and silicon-based negative electrode active materials, the problems of insufficient energy density and long charging time of lithium secondary batteries are solved, and the charging/discharge characteristics of high capacity and high-rate are achieved.

CN119768930APending Publication Date: 2025-04-04LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480003779.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-15
Filing Date
2024-06-11
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing lithium secondary batteries have problems such as insufficient energy density, long charging time and poor discharge performance under high power conditions during charging and discharging.

Method used

The negative electrode active layer with a two-layer structure is adopted. The first layer includes the first carbon-based negative electrode active material, the second layer includes the second carbon-based negative electrode active material and the silicon-based negative electrode active material. The arrangement value of the carbon-based negative electrode active material and the X-ray diffraction peak area ratio of the silicon-based negative electrode active material are adjusted through magnetic field treatment to optimize the migration channel of lithium ions.

Benefits of technology

The high capacity and high-rate charging/discharge characteristics of lithium secondary batteries are realized, which shortens the charging time and improves the energy density and life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005283609400000221
    Figure BDA0005283609400000221
Patent Text Reader

Abstract

Disclosed herein are a negative electrode for a lithium secondary battery and a method of manufacturing the same, in which the negative electrode exhibits high charge and discharge capacities by including a carbon-based negative electrode active material and a silicon-based negative electrode active material together in a negative electrode active layer. Furthermore, the negative electrode active layer of the negative electrode has a double-layer structure, but by adjusting i) the arrangement value (O.I) of the carbon-based negative electrode active material and ii) the X-ray diffraction peak area ratio of the arrangement value (O.I) and the silicon-based negative electrode active material of the second negative electrode active layer located at the outermost portion so as to satisfy a predetermined range, the X-ray diffraction peak area ratio of the carbon-based negative electrode active material and the silicon-based negative electrode active material satisfies a predetermined range. The negative electrode has the advantage of effectively improving the high-rate charge and discharge characteristics of the lithium secondary battery comprising the negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to Korean Patent Application No. 10-2023-0076642, filed on Jun. 15, 2023, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] The invention relates to a negative electrode for a lithium secondary battery and a method for manufacturing the same. Background Art

[0004] In recent years, lithium secondary batteries have been widely used not only in small devices such as portable electronic devices, but also in medium and large devices such as battery packs or power storage devices for hybrid and electric vehicles. In particular, with the increase in environmental issues in recent years, a lot of research has been conducted on electric vehicles and hybrid electric vehicles, which can replace vehicles using fossil fuels, such as gasoline and diesel vehicles, which are the main source of air pollution.

[0005] Conventional lithium secondary batteries are limited to short-range electric vehicles due to limited energy density. Therefore, technologies for increasing the energy density of lithium secondary batteries have been intensively developed.

[0006] However, the developed automotive lithium secondary batteries have the following problems: the time to charge after driving the vehicle is long after discharging. Therefore, as the penetration rate of electric vehicles increases, it is necessary to shorten the charging time to a level acceptable to users. In addition, electric vehicles need to be able to cope with high power situations (such as rapid acceleration). This requires lithium secondary batteries to have high rate discharge performance, but there is no technology that can meet this requirement.

[0007] Meanwhile, a lithium secondary battery is a rechargeable electric energy generating device consisting of a laminated structure of a positive electrode, a separator, and a negative electrode. When a lithium secondary battery is charged, a lithium deintercalation reaction is initiated at the positive electrode of the battery, in which the lithium contained in the positive electrode active material is oxidized and released, and a lithium intercalation reaction occurs at the negative electrode, in which the lithium is reduced and enters the negative electrode active material. Generally, the deintercalation reaction in the positive electrode active material is faster than the intercalation reaction in the negative electrode active material, so the fast charging and discharging properties of the lithium secondary battery are mainly determined by the negative electrode.

[0008] Materials containing graphite are widely used as negative electrode active materials for negative electrodes. The average potential for releasing lithium from materials containing graphite is about 0.2 V (based on Li / Li +), and the discharge potential is relatively flat. Therefore, when graphite is used as the negative electrode active material, the voltage of the secondary battery is high and constant. However, the capacity per unit mass of graphite material is small, at 372 mAh / g. On the other hand, the capacity of graphite material has been increased to close to the above theoretical capacity, so it is difficult to further increase the capacity. In addition, when graphite is used as the negative electrode active material, the insertion reaction of lithium ions proceeds slowly, which limits the fast charging performance compared with other negative electrode active materials.

[0009] In order to improve the high capacity and fast charging performance of lithium secondary batteries, various negative electrode active materials are being studied. For example, silicon has been the subject of recent research because it has been found that silicon can reversibly adsorb and release large amounts of lithium by reacting with lithium compounds. The theoretical maximum capacity of silicon is about 4020mAh / g (9800mAh / cc, specific gravity is 2.23), which is very large compared to graphite materials, so it is a favorable advantage as a high energy density and / or high capacity negative electrode material. However, the limitation of silicon is that it causes a large volume change (~300%) during charging and discharging, and does not have high rate discharge characteristics, so the life and fast discharge efficiency of lithium secondary batteries containing silicon are not high.

[0010] Therefore, negative electrode technology that can simultaneously achieve high capacity characteristics and high-rate charge and discharge characteristics is needed to fundamentally solve these problems. Summary of the invention

[0011] [Technical issues]

[0012] An object of the present invention is to provide a negative electrode for a lithium secondary battery, which can simultaneously achieve high capacity characteristics and high rate charge / discharge characteristics, and also provide a method for manufacturing the negative electrode and a lithium secondary battery including the negative electrode.

[0013] [Technical solution]

[0014] In order to solve the above problems, in one exemplary embodiment, the present invention provides a negative electrode for a lithium secondary battery, comprising:

[0015] Anode current collector;

[0016] a first negative electrode active layer, which is disposed on at least one side of the negative electrode current collector and comprises a first carbon-based negative electrode active material; and

[0017] The second negative electrode active layer is disposed on the first negative electrode active layer and comprises a second carbon-based negative electrode active material and a silicon-based negative electrode active material, wherein:

[0018] The arrangement value (OI) of the carbon-based negative electrode active material of the second negative electrode active layer according to the following formula 1 is 2.5 or less, and satisfies the following formula 2 to be 8 or less:

[0019] [Formula 1]

[0020] OI=I 004 / I 110

[0021] [Formula 2]

[0022] I Si *OI

[0023] In equation 1 and equation 2,

[0024] I 004 represents the peak area representing the (0,0,4) crystal plane in the X-ray diffraction (XRD) spectrum measurement of the negative electrode active layer,

[0025] I 110 represents the peak area representing the (1,1,0) crystal plane in the X-ray diffraction (XRD) spectrum measurement of the negative electrode active layer,

[0026] I Si It represents the area ratio of the peak representing the (1,1,1) crystal plane of the silicon-based negative electrode active material in the X-ray diffraction (XRD) spectrum analysis of the negative electrode active layer.

[0027] Here, the arrangement value (OI) of the carbon-based negative electrode active material of the second negative electrode active layer may be 0.1 to 1.5, and satisfy Formula 2 of 0.7 to 6.

[0028] In addition, the first carbon-based negative electrode active material and the second carbon-based negative electrode active material respectively contain at least one of natural graphite and artificial graphite.

[0029] In addition, the silicon-based negative electrode active material may include silicon (Si), silicon carbide (SiC) and silicon oxide (SiO q , wherein 0.8≤q≤2.5) is at least one of the following.

[0030] The silicon-based negative electrode active material may be included in an amount of 1 wt % to 40 wt % relative to the total weight of the negative electrode active materials included in the first negative electrode active layer and the second negative electrode active layer.

[0031] In addition, the average particle size (Dc) of the second carbon-based negative electrode active material is 1 μm to 50 μm, and the average particle size (Ds) of the silicon-based negative electrode active material is 0.1 μm to 10 μm, wherein the average particle size ratio (Dc / Ds) of the second carbon-based negative electrode active material to the silicon-based negative electrode active material can be 2 to 10.

[0032] In addition, the second negative electrode active layer may include 1 wt % to 40 wt % of the silicon-based negative electrode active material based on the weight of the entire negative electrode active layer.

[0033] In addition, in an exemplary embodiment, the present invention provides a method for manufacturing a negative electrode for a lithium secondary battery, comprising:

[0034] applying a first negative electrode slurry and a second negative electrode slurry such that the first negative electrode slurry is located on at least one surface of the negative electrode current collector and the second negative electrode slurry is located on the first negative electrode slurry;

[0035] applying a magnetic field to the applied first negative electrode slurry and second negative electrode slurry; and

[0036] The first negative electrode slurry and the second negative electrode slurry to which the magnetic field is applied are dried to form a negative electrode active layer, wherein:

[0037] The first negative electrode slurry comprises a first carbon-based negative electrode active material,

[0038] The second negative electrode slurry comprises a second carbon-based negative electrode active material and a silicon-based negative electrode active material, wherein:

[0039] The magnetic field is applied at a strength of 10,000 G or less.

[0040] Here, the step of applying the magnetic field may be performed for a period of 1 second to 20 seconds.

[0041] Furthermore, in an exemplary embodiment, the present invention provides a lithium secondary battery including an electrode assembly including a positive electrode, the negative electrode of the above embodiment, and a separator disposed between the positive electrode and the negative electrode.

[0042] Here, the positive electrode may include a positive electrode active layer, which includes one or more positive electrode active materials of lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2 and is disposed on at least one side of the positive electrode current collector:

[0043] [Chemical formula 1]

[0044] Li x [Ni y Co z Mn w M 1 v ]O2

[0045] [Chemical formula 2]

[0046] LiM 2 p Mn 1-p O4

[0047] In Chemical Formula 1 and Chemical Formula 2,

[0048] M 1is at least one element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo,

[0049] x, y, z, w, and v are respectively 1.0 ≤ x ≤ 1.30, 0.5 ≤ y < 1, 0 < z ≤ 0.3, 0 < w ≤ 0.3, and 0 ≤ v ≤ 0.1, where y + z + w + v = 1,

[0050] M 2 is Ni, Co, or Fe, and

[0051] p is 0.05 ≤ p ≤ 1.0

[0052] As an example, the positive electrode active material may include one or more of the following: LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2, LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2, LiNi 0.7 Mn 1.3 O4, LiNi 0.5 Mn 1.5 O4, and LiNi 0.3 Mn 1.7 O4.

[0053] Meanwhile, the electrode assembly may be a stacked electrode assembly; a folded electrode assembly; or a folded-stacked electrode assembly.

[0054] [Beneficial Effects]

[0055] The negative electrode for lithium secondary battery of the present invention contains silicon-based negative electrode active material together with carbon-based negative electrode active material in the negative electrode active layer, and exhibits high charge and discharge capacity. In addition, the negative electrode active layer of the negative electrode has a double-layer structure, but by adjusting the arrangement value (OI) of the second negative electrode active layer located at the outermost part of i) carbon-based negative electrode active material and ii) the arrangement value (OI) and the specific X-ray diffraction peak area ratio of the silicon-based negative electrode active material to meet the predetermined range, it has the advantage of effectively improving the high-rate charge and discharge characteristics of the lithium secondary battery containing the negative electrode. DETAILED DESCRIPTION

[0056] The present invention is susceptible to various modifications and may have a variety of embodiments, some of which are described in detail below.

[0057] However, this is not intended to limit the present invention to any specific embodiment, and should be construed to include all modifications, equivalents, or substitutes falling within the scope of the idea and technology of the present invention.

[0058] The terms "include / comprise" or "have" are used herein to specify the presence of features, quantities, steps, actions, components or members, or a combination thereof, described in the specification, and it should be understood that the possibility of the presence or addition of one or more other features, quantities, steps, actions, components, members, or a combination thereof is not precluded.

[0059] In addition, when a portion of a layer, film, region or plate is disposed "on" another portion, this includes not only a case where one component is disposed "directly" "on" another component, but also a case where a third component is interposed therebetween. Conversely, when a portion of a layer, film, region or plate is disposed "below" another portion, this includes not only a case where one component is disposed "directly" "below" another component, but also a case where a third component is interposed therebetween. In addition, in the present application, "on" may include not only a case where it is disposed on an upper portion, but also a case where it is disposed on a lower portion.

[0060] In addition, in the present invention, "comprising ... as a main component" may mean that the specified component is contained at 50% by weight (or 50% by volume) or more, 60% by weight (or 60% by volume) or more, 70% by weight (or 70% by volume) or more, 80% by weight (or 80% by volume) or more, 90% by weight (or 90% by volume) or more, or 95% by weight (or 95% by volume) or more relative to the total weight (or total volume). For example, "comprising graphite as a main component of the negative electrode active material" may mean that at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or at least 95% by weight of graphite is contained based on the total weight of the negative electrode active material, and in some cases may mean that the entire negative electrode active material is composed of graphite and contains 100% of graphite.

[0061] In addition, as used herein, "the carbon-based negative electrode active material has an orientation" or "the carbon-based negative electrode active material is arranged" means that a certain crystal plane (for example, the ab axis crystal plane of graphite) representing the two-dimensional planar structure of the carbon-based negative electrode active material constituting the negative electrode active material particles is arranged to have a predetermined inclination relative to the surface of the negative electrode current collector, which may be different from the carbon-based negative electrode active material particles themselves being arranged in the negative electrode active layer to have a specific orientation.

[0062] In addition, "highly oriented carbon-based negative electrode active material" may mean that a certain crystal plane (e.g., ab axis crystal plane of graphite) representing the two-dimensional planar structure of the carbon-based negative electrode active material contained in the negative electrode active layer has a high frequency of having a predetermined inclination relative to the negative electrode current collector surface. It also means that in some cases, the crystal planes of the carbon-based negative electrode active material contained in the negative electrode active layer are arranged at a large angle relative to the negative electrode current collector surface (e.g., close to a right angle, greater than 45°; more specifically, greater than 60°).

[0063] In addition, "a high arrangement value of a carbon-based negative electrode active material" may refer to a larger value of the "arrangement value (OI)" described herein, which means that a certain crystal plane representing the two-dimensional planar structure of the carbon-based negative electrode active material contained in the negative electrode active layer (e.g., the ab axis crystal plane of graphite) is arranged at a smaller angle (e.g., less than 45°) relative to the surface of the negative electrode current collector. Conversely, "a low arrangement value of a carbon-based negative electrode active material" may mean that the value of the "arrangement value (OI)" is smaller, so that the crystal planes of the carbon-based negative electrode active material contained in the negative electrode active layer are arranged at a larger angle (e.g., close to a right angle, greater than 45°; more specifically, greater than 60°) relative to the surface of the negative electrode current collector.

[0064] In addition, as used herein, "crystal plane of carbon-based negative electrode active material" refers to the plane where the atoms of the carbon-based negative electrode active material form a crystal shape, which in the present invention may represent a crystal plane containing a plane of the carbon-based negative electrode active material, or a crystal plane containing the a-axis / b-axis / ab-axis of the carbon-based negative electrode active material crystal.

[0065] In addition, as used herein, the average particle size (D 50 The term “median diameter” refers to the particle size at which the sum of the particle size distribution of the particles is 50%, also known as the median diameter.

[0066] The present invention will now be described in more detail.

[0067] Negative electrode for lithium secondary battery

[0068] In one exemplary embodiment, the present invention provides a negative electrode for a lithium secondary battery, comprising:

[0069] Anode current collector;

[0070] A first negative electrode active layer, which is disposed on at least one side of the negative electrode current collector and includes a first carbon-based negative electrode active material; and

[0071] The second negative electrode active layer is disposed on the first negative electrode active layer and comprises a second carbon-based negative electrode active material and a silicon-based negative electrode active material, wherein:

[0072] The arrangement value (OI) of the carbon-based negative electrode active material of the second negative electrode active layer according to the following formula 1 is 2.5 or less, and satisfies the following formula 2 to be 8 or less:

[0073] [Formula 1]

[0074] OI=I 004 / I 110

[0075] [Formula 2]

[0076] I Si *OI

[0077] In equation 1 and equation 2,

[0078] I 004 represents the peak area representing the (0,0,4) crystal plane in the X-ray diffraction (XRD) spectrum measurement of the negative electrode active layer, I 110 It represents the peak area representing the (1,1,0) crystal plane in the X-ray diffraction (XRD) spectrum measurement of the negative electrode active layer.

[0079] I Si It represents the area ratio of the peak representing the (1,1,1) crystal plane of the silicon-based negative electrode active material in the X-ray diffraction (XRD) spectrum analysis of the negative electrode active layer.

[0080] The negative electrode for lithium secondary battery of the present invention comprises a negative electrode active layer located on at least one side of the negative electrode current collector. The negative electrode active layer is a layer that realizes the electrical activity of the negative electrode and contains a negative electrode active material as a main component that realizes electrochemical redox reaction during the charge and discharge process of the battery.

[0081] In this case, the negative electrode active layer may have a double-layer structure in which a first negative electrode active layer and a second negative electrode active layer are sequentially stacked on a negative electrode current collector. Since the composition of each layer in the negative electrode active layer having a double-layer structure can be easily controlled, the type and content of the components contained in each layer can be controlled according to a specific purpose (such as improving the energy efficiency of the battery or improving the adhesion between the active layer and the current collector) to improve the performance of the negative electrode. For example, the negative electrode active layer may selectively include a silicon-based negative electrode active material that enables the battery to have a higher charge and discharge capacity only in the second negative electrode active layer facing the positive electrode. In addition, the negative electrode active layer may selectively include a negative electrode active material (such as natural graphite) that has good adhesion only to the first negative electrode active layer in contact with the negative electrode current collector, or may include a higher content of a binder that imparts adhesion to the components constituting the active layer.

[0082] In the present invention, the first negative electrode active layer comprises a first carbon-based negative electrode active material, and the second negative electrode active layer comprises a second carbon-based negative electrode active material and a silicon-based negative electrode active material.

[0083] In this case, the types and / or contents of the first carbon-based negative electrode active material and the second carbon-based negative electrode active material contained in each negative electrode active layer may be the same and / or different. Specifically, the first carbon-based negative electrode active material and the second carbon-based negative electrode active material refer to materials having carbon atoms as their main components, and such carbon-based negative electrode active materials may include graphite. Graphite may include one or more of natural graphite and artificial graphite. For example, the first carbon-based negative electrode active material and the second carbon-based negative electrode active material may contain only natural graphite or artificial graphite, or in some cases, a mixture of natural graphite and artificial graphite. In this case, the weight ratio of natural graphite to artificial graphite may be 5 to 50:50 to 95, or 20 to 45:55 to 80. By including natural graphite and artificial graphite in a mixing ratio as described above, the carbon-based negative electrode active material can achieve a high orientation of the carbon-based negative electrode active material relative to the surface of the negative electrode current collector, while strengthening the bonding of the negative electrode current collector to the negative electrode active layer.

[0084] In one example, the first carbon-based negative active material may include natural graphite and artificial graphite in a weight ratio of 30 to 50:50 to 70, and the second carbon-based negative active material may include only artificial graphite.

[0085] In addition, the first carbon-based negative electrode active material and the second carbon-based negative electrode active material are preferably spherical graphite assemblies formed by a plurality of flake graphites. Flake graphite can be natural graphite, artificial graphite, calcined carbon (blocky mesophase) based on tar and asphalt, graphitized coke (coarse coke, raw coke, asphalt coke, needle coke, petroleum coke, etc.), etc., in particular, the graphite assembly is preferably assembled using a plurality of highly crystalline natural graphites. In addition, a graphite assembly can be formed by 2 to 100, preferably 3 to 20 flake graphites.

[0086] This carbon-based active material (specifically graphite) can be in the shape of spherical particles, wherein the sphericity of the graphite particles can be greater than or equal to 0.75, for example, 0.75 to 1.0; 0.75 to 0.95; 0.8 to 0.95; or 0.90 to 0.99. Here, "sphericity" can refer to the ratio of the shortest diameter (short diameter) to the longest diameter (long diameter) in any diameter passing through the center of the particle. A sphericity of 1 indicates that the particle is spherical in shape. The sphericity can be measured and determined using a particle shape analyzer, or measured using a scanning electron microscope (SEM) or an energy dispersive spectrometer and analyzed to determine the shape of the particles.

[0087] The present invention can achieve high conductivity of the negative electrode active layer by making the shape of the first carbon-based negative electrode active material and the second carbon-based negative electrode active material close to spherical. Therefore, the negative electrode containing the spherical carbon-based negative electrode active material can improve the capacity of the secondary battery and has the advantage of increasing the specific surface area per unit weight of the negative electrode active material, which can improve the adhesion between the negative electrode active layer and the current collector.

[0088] In addition, the silicon-based negative electrode active material is a material containing silicon (Si) as a main component and is contained only in the second negative electrode active layer. The present invention is able to improve the charge and discharge capacity of the negative electrode by including the silicon-based negative electrode active material in the second negative electrode active layer adjacent to the positive electrode active layer. In addition, when the silicon-based negative electrode active material is contained in the first negative electrode active layer, there is a problem of reduced durability of the negative electrode due to the large volume change of the silicon-based negative electrode active material during charging and discharging. However, the present invention is able to maintain high durability of the negative electrode by applying the silicon-based negative electrode active material to the second negative electrode active layer.

[0089] Such silicon-based negative electrode active materials include silicon (Si), silicon carbide (SiC), silicon monoxide (SiO) or silicon dioxide (SiO2), which can be contained in the second negative electrode active layer alone or in combination. When silicon monoxide (SiO2) and silicon dioxide (SiO2) are uniformly mixed or compounded and contained in the negative electrode active layer as silicon-based negative electrode active materials, they can be expressed as silicon oxide (SiO q , where 0.8≤q≤2.5).

[0090] In addition, the silicon-based negative electrode active material can be doped with Li, Mg, Al, Ca, Ti, etc., or alloyed therewith. In addition, the silicon-based negative electrode active material can be surface-treated with a carbon coating layer, etc., to suppress volume expansion during charging in the presence of oxygen (O) while improving the conductivity of the negative electrode active material.

[0091] In addition, based on 100 parts by weight of the entire negative electrode active layer, the carbon-based negative electrode active material and the silicon-based negative electrode active material contained in each layer of the negative electrode active layer may account for at least 85 parts by weight. Specifically, based on 100 parts by weight of the total weight of the negative electrode active layer, the carbon-based negative electrode active material and the silicon-based negative electrode active material in each layer of the negative electrode active layer may account for at least 90 parts by weight, at least 93 parts by weight, or at least 95 parts by weight.

[0092] In addition, relative to the total weight of all negative electrode active materials contained in the first negative electrode active layer and the second negative electrode active layer, the content of the silicon-based negative electrode active material may be 0.1 wt % to 40 wt %, and may be 0.5 wt % to 20 wt %, 1 wt % to 9 wt %, 5 wt % to 15 wt %, 3 wt % to 7 wt %, 11 wt % to 19 wt %, 13 wt % to 17 wt %, 15 wt % to 20 wt %, 10 wt % to 30 wt %, 20 wt % to 40 wt %, 25 wt % to 35 wt %, 15 wt % to 25 wt %, or 9 wt % to 22 wt %. By adjusting the total content ratio of all negative electrode active materials contained in the negative electrode active layer and the content ratio of the silicon-based negative electrode active material contained in all negative electrode active materials to the above range, the present invention can improve the charge capacity per unit mass while reducing lithium consumption and irreversible capacity loss during the initial charge and discharge process of the secondary battery. Furthermore, by minimizing the volume change of the negative electrode active layer during the charge and discharge process of the secondary battery, the structural stability of the negative electrode active layer can be improved, thereby increasing the life of the secondary battery.

[0093] In addition, the negative electrode of the present invention can further improve its high rate charge and discharge characteristics by controlling the crystal structure characteristics of the negative electrode active material contained in the second negative electrode active layer adjacent to the positive electrode.

[0094] In one example, the arrangement value (OI) of the second carbon-based negative electrode active material included in the second negative electrode active layer according to the following Formula 1 may be 2.5 or less:

[0095] [Formula 1]

[0096] OI=I 004 / I 110

[0097] In formula 1,

[0098] I 004 represents the peak area representing the (0,0,4) crystal plane in the X-ray diffraction (XRD) spectrum measurement of the negative electrode active layer, I 110 It represents the peak area representing the (1,1,0) crystal plane in the X-ray diffraction (XRD) spectrum measurement of the negative electrode active layer.

[0099] The arrangement value (OI) of the second carbon-based negative electrode active material can be an indicator of the degree of orientation of the ab-axis crystal plane of the carbon-based negative electrode active material in a specific direction (specifically relative to the surface of the negative electrode current collector) when measured by X-ray diffraction (XRD). Specifically, in the X-ray diffraction measurement, for the second carbon-based negative electrode active material, i.e., graphite, the second negative electrode active layer exhibits the following peaks: 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2°. These represent the (0,0,2), (1,0,0), (1,0,1)R, (1,0,1)H, (0,0,4), and (1,1,0) planes of graphite. The peak at 2θ=43.4±0.2° can also be considered as the overlap of the peak corresponding to the (1,0,1) R plane of the second carbon-based negative active material and the peak of the (1,1,1) plane of the current collector (eg, copper (Cu)).

[0100] Among them, the area ratio obtained by integrating the relative intensity of the peak at 2θ=54.7±0.2° representing the (0,0,4) plane and the peak at 2θ=77.5±0.2° representing the (1,1,0) plane can be used to measure the arrangement value (OI) of the second carbon-based negative electrode active material.

[0101] Since the peak at 2θ=54.7±0.2° is a peak representing a crystal plane having an inclination relative to the negative electrode current collector of the second carbon-based negative electrode active material, when the arrangement value (OI) is close to 0, it can be indicated that the inclination relative to the surface of the negative electrode current collector is closer to 90°, and when the arrangement value (OI) is large, the inclination relative to the surface of the negative electrode current collector is closer to 0° or 180°. In other words, the arrangement of the second negative electrode active layer of the present invention can make the angle of the second carbon-based negative electrode active material relative to the negative electrode current collector be 60° or more, 70° or more, 70° to 90°, 80° to 90°, 65° to 85° or 70° to 85°. Therefore, the arrangement value (OI) of the second carbon-based negative electrode active material of the second negative electrode active layer can be lower than when the second carbon-based negative electrode active material is arranged at a lower angle of less than 60°. As an example, the arrangement value (OI) of the carbon-based negative electrode active material of the second negative electrode active layer according to Formula 1 may be 2.5 or less, 2.0 or less, 1.3 or less, 1.0 or less, 0.5 or less, 0.1 to 2.5, 0.1 to 2.0, 0.1 to 1.5, 0.2 to 1.3, 0.4 to 1.3, 0.4 to 1.3, 0.4 to 1.0, 0.5 to 1.3, 1.1 to 1.3, 0.5 to 0.9 or 0.4 to 0.6. Here, the arrangement value (OI) indicates the arrangement of the ab axis crystal plane of the carbon-based negative electrode active material, and does not indicate the degree to which the carbon-based negative electrode active material particles are arranged by rotating themselves in the active layer.

[0102] By adjusting the arrangement value (OI) of the second carbon-based negative electrode active material contained in the second negative electrode active layer to be as described above, the present invention can obtain a lithium ion migration channel in which lithium ions can migrate at a shorter distance inside the negative electrode active layer. As a result, the negative electrode of the present invention can prevent the increase in resistance caused by the long migration distance of lithium ions, thereby preventing the high-rate charging performance from deteriorating due to resistance, and at the same time improving the high-rate discharge efficiency.

[0103] As another example, the second positive electrode active layer may satisfy the following formula 2 with a value of 8 or less:

[0104] [Formula 2]

[0105] I Si *OI

[0106] In formula 2,

[0107] OI represents the arrangement value of the second carbon-based negative electrode active material according to Formula 1,

[0108] I Si It represents the area ratio of the peak representing the (1,1,1) crystal plane of the silicon-based negative electrode active material in the X-ray diffraction (XRD) spectrum analysis of the negative electrode active layer.

[0109] In pure silicon having a crystalline phase, the distance or density between silicon elements forming the crystal varies depending on the type of crystal plane. Therefore, pure silicon (Si) having a crystalline phase may exhibit different electrical properties (e.g., electron mobility) depending on the orientation (i.e., crystal direction) of each crystal plane exposed to the surface. For example, among the crystal directions of a silicon crystal, (1,0,0), (1,1,1), and (1,1,0) may exhibit high electron mobility in the order of (1,0,0)>(1,1,1)>(1,1,0), and the embedding of metal ions may exhibit the order of (1,1,0)>(1,1,1)>(1,0,0).

[0110] Therefore, the present invention is characterized in that the (1,1,1) plane of the crystal plane of pure silicon having a crystalline phase is controlled to exhibit the characteristics. Specifically, in the X-ray diffraction (XRD) spectrum analysis, the second negative electrode active layer of the present invention exhibits a diffraction peak representing the silicon-based negative electrode active material and a diffraction peak representing the crystal plane of the second carbon-based negative electrode active material. For example, if the silicon-based negative electrode active material is silicon oxide (SiO q , where 0.8≤q≤2.5), the X-ray diffraction measurement of the second negative active layer shows a smooth and broad curved spectrum indicating amorphous silicon oxide, and peaks 2θ=28.4±0.2°, 47.3±0.5° and 56.1±0.2° indicating pure Si, respectively. These peaks represent the (1,1,1), (2,2,0) and (3,1,1) crystal planes of pure Si, respectively.

[0111] In this case, as the ab-axis crystal plane of the second carbon-based negative electrode active material is arranged at a larger angle relative to the surface of the negative electrode current collector, the intensity of the diffraction peak representing the (1,1,1) crystal plane of pure Si becomes stronger, and the area value obtained by integrating the entire peak intensity may also show an increasing trend. This indicates that the (1,1,1) crystal plane of silicon is more exposed on the surface of the second negative electrode active layer. However, as described above, the exposure degree of the (1,1,1) crystal plane may affect the mobility of electrons and metal ions, and the mobility of electrons and metal ions may be a trade-off relationship, so it is preferred that the exposure degree of the (1,1,1) crystal plane is controlled to meet a predetermined range.

[0112] Therefore, the present invention achieves this by adjusting Formula 2 to 8 or less. Specifically, the second negative electrode active layer can satisfy the following Formula 2: 7 or less; 6 or less; 4 or less; 3.5 or less; 3 or less; 0.7 to 8; 0.7 to 6; 1 to 6; 1.75 to 6; 1.75 to 4; 1.75 to 3.5; 1.75 to 3; 1.75 to 2.5; 1.75 to 2.1; 2 to 6; 2 to 4; 2.1 to 3.5; 2.1 to 3.1; 3 to 5; or 2.5 to 3. Here, Formula 2 indicates that the arrangement value (OI) of Formula 1 is calculated from the diffraction peak of the second carbon-based negative electrode active material in the X-ray diffraction spectrum analysis of the second negative electrode active layer, and the calculated arrangement value (OI) is reflected in the area integral of the diffraction peak intensity of the (1,1,1) plane representing the silicon-based negative electrode active material. By making Formula 2 satisfy the above range, the present invention can significantly increase the lithium ion mobility and embedding performance of the second negative electrode active layer comprising a second carbon-based negative electrode active material and a silicon-based negative electrode active material, thereby significantly increasing the high-rate charge and discharge efficiency of the secondary battery comprising the second negative electrode active layer.

[0113] In addition, the second carbon-based negative electrode active material and the silicon-based negative electrode active material contained in the second negative electrode active layer may have a predetermined particle size. Specifically, the average particle size (Dc) of the second carbon-based negative electrode active material may be 1 μm to 50 μm, the average particle size (Ds) of the silicon-based negative electrode active material may be 0.1 μm to 10 μm, and the ratio of the average particle size of the second carbon-based negative electrode active material to the silicon-based negative electrode active material (Dc / Ds) may be 2 to 10.

[0114] Specifically, the average particle size (D 50 , Dc) can be 1 μm to 50 μm, and can be selectively applied within this range to match the average thickness of the second negative electrode active layer. For example, the average particle size (Dc) of the second carbon-based negative electrode active material 50) can be 1μm to 40μm; 1μm to 30μm; 10μm to 40μm; 15μm to 30μm; 25μm to 50μm; 11μm to 19μm; 15μm to 25μm; 20μm to 30μm; 1μm to 20μm; 1μm to 10μm; 5μm to 15μm; 10μm to 20μm; 15μm to 30μm; 15μm to 20μm; 21μm to 26μm; 25μm to 30μm; 11μm to 17μm; 16μm to 23μm; 2μm to 7μm; 0.5μm to 5μm; or 1μm to 3μm. The spherical second carbon-based negative electrode active material can benefit from a smaller particle size to maximize the disorder in the expansion direction of each particle, thereby preventing the particles from expanding when charged with lithium ions. However, if the particle size of the second carbon-based negative electrode active material is less than 1.0 μm, a large amount of binder is required due to the increase in the number of particles per unit volume, and the sphericity and sphericity yield may be low. On the other hand, if the average particle size exceeds 50 μm, the expansion rate of the negative electrode active material increases significantly during the charging and discharging process of the secondary battery, so with repeated charging and discharging, the adhesion between the negative electrode active material particles and the adhesion between the negative electrode active material particles and the current collector may be reduced, resulting in a significant reduction in the cycle characteristics.

[0115] In addition, the average particle size (D 50 , Ds) may be 0.1 μm to 10 μm, more specifically, the average particle size (D 50 ) is 0.1μm to 5μm; 0.1μm to 3μm; 0.1μm to 1μm; 0.5μm to 2μm; 0.5μm to 5μm; 1μm to 5μm; 3μm to 7μm; 5μm to 10μm; 1μm to 3μm; 4μm to 9μm; 0.1μm to 0.9μm; 0.8μm to 1.2μm; or 0.3μm to 0.8μm.

[0116] When the average particle size of the silicon-based negative electrode active material is less than 0.1 μm, it is difficult to uniformly disperse the second negative electrode active layer, and with the charging and discharging of the secondary battery, the redox reaction of the agglomerated area and the non-agglomerated area of ​​the silicon-based negative electrode active material is unevenly induced, which may promote the degradation of the second negative electrode active layer. In addition, when the average particle size of the silicon-based negative electrode active material exceeds 10 μm, it is difficult to control the crystal plane of the silicon-based negative electrode active material, and during the charging and discharging process of the secondary battery, the expansion rate per unit area of ​​the second negative electrode active layer increases significantly, resulting in a significant decrease in the cycle characteristics with repeated charging and discharging.

[0117] In addition, the average particle size ratio (Dc / Ds) of the second carbon-based negative electrode active material to the silicon-based negative electrode active material may be 2 to 10, more specifically 2 to 7; 2 to 5; 3 to 7; 4 to 8; 5 to 10; or 6 to 9.

[0118] By making the ratio of the average particle size of the second carbon-based negative electrode active material to the silicon-based negative electrode active material (Dc / Ds) satisfy the above range, the present invention can induce a structure in which the silicon-based negative electrode active material is filled in the gaps formed by the plurality of second carbon-based negative electrode active materials. In this case, the gap acts as a buffer to buffer the volume expansion of the silicon-based negative electrode active material during the charging and discharging process of the secondary battery, thereby minimizing the volume expansion of the second negative electrode active layer.

[0119] In addition, when the average particle size ratio (Dc / Ds) is less than the lower limit of the above range, the influence of the second carbon-based negative electrode active material on the silicon-based negative electrode active material is reduced, and it is difficult to control the crystal plane of pure silicon with a crystalline phase. In addition, if the average particle size ratio (Dc / Ds) exceeds the upper limit of the above range, the second negative electrode active layer accelerates degradation during the charging and discharging process of the secondary battery, thereby shortening its service life.

[0120] At the same time, the average thickness of the negative electrode active layer can be 100 μm to 300 μm. Specifically, the average thickness of the negative electrode active layer can be 100 μm to 250 μm; 100 μm to 250 μm; or 130 μm to 190 μm. By adjusting the average thickness of the negative electrode active layer to the above range, the present invention can easily control the crystallization characteristics of the negative electrode active material contained in the second negative electrode active layer, thereby improving the high rate charge and discharge characteristics of the secondary battery containing the negative electrode of the present invention.

[0121] In addition, the average thickness of the first negative electrode active layer and the second negative electrode active layer may be the same or different. Specifically, the ratio of the average thickness (D1) of the first negative electrode active layer to the average thickness (D2) of the second negative electrode active layer may be 1:0.5 to 3, or more specifically, 1:0.8 to 2.5, 1:1 to 2.5, 1:1.1 to 2, 1:0.9 to 1.1, or 1:1.5 to 3. By adjusting the ratio of the average thickness of the first negative electrode active layer to the average thickness of the second negative electrode active layer to the above range, the present invention can maximize the charge / discharge capacity while maintaining high durability of the negative electrode.

[0122] Furthermore, in addition to the negative electrode active material as a main component, the first negative electrode active layer and the second negative electrode active layer of the present invention may optionally contain a conductive material, a binder, other additives, and the like as required.

[0123] The conductive material may include one or more of carbon black, acetylene black, Ketjen black, carbon nanotubes, carbon fibers, etc., but is not limited thereto.

[0124] In one example, the negative electrode active layer may include carbon black, carbon nanotubes, carbon fibers, etc. as the conductive material alone or in combination.

[0125] In this case, the content of the conductive material may be 0.1 to 10 parts by weight based on 100 parts by weight of the negative electrode active layer. Specifically, the content of the conductive material may be 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, 2 to 6 parts by weight, or 0.5 to 2 parts by weight based on 100 parts by weight of the negative electrode active layer. By controlling the content of the conductive material within the range described above, the present invention can prevent the reduction in charge capacity due to low content of the conductive material and increased resistance of the negative electrode, and can prevent the reduction in charge capacity due to excessive conductive material and reduced content of the negative electrode active material, or the reduction in fast charge characteristics due to increased load on the negative electrode active layer.

[0126] In addition, the binder can be appropriately applied as a component that helps the bonding of the negative electrode active material to the conductive material, etc. and to the current collector to a degree that does not deteriorate the electrical properties of the electrode, and specifically, the binder may include one or more selected from the group consisting of: vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile and polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene butadiene rubber (SBR) and fluorinated rubber.

[0127] Based on 100 parts by weight of the negative electrode active layer, the content of the binder may be 0.1 to 10 parts by weight. More specifically, based on 100 parts by weight of the negative electrode active layer, the content of the binder may be 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight. By controlling the content of the binder in the negative electrode active layer within the above range, the present invention can prevent the adhesion of the active layer from being deteriorated due to the low content of the binder, or prevent the electrical properties of the electrode from being deteriorated due to excessive binder.

[0128] In addition, the negative electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, nickel, titanium, calcined carbon, etc. can be used, and in the case of copper or stainless steel, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can also be used. In addition, considering the conductivity and total thickness of the negative electrode to be manufactured, the average thickness of the negative electrode current collector can be appropriately applied to be 1 to 500 μm.

[0129] Lithium secondary battery

[0130] In addition, in one embodiment, the present invention provides a lithium secondary battery including an electrode assembly, which includes a positive electrode, the negative electrode of the present invention as described above, and a separator disposed between the positive electrode and the negative electrode.

[0131] The lithium secondary battery of the present invention includes an electrode assembly having a structure in which a plurality of positive electrodes and a plurality of negative electrodes are alternately arranged and a separator is located therebetween. The lithium secondary battery having the negative electrode of the present invention as described above not only has a high charge and discharge capacity, but also has excellent high-rate charge and discharge characteristics, and thus can be used as a power source for medium and large-sized devices such as electric vehicles.

[0132] In this case, the negative electrode has the same structure as the above-described structure, and thus a detailed description thereof is omitted.

[0133] In addition, the positive electrode may include a positive electrode active layer including a positive electrode active material on a positive electrode current collector. Optionally, according to need, the positive electrode active layer may further optionally include a conductive material, a binder, other additives, and the like.

[0134] The positive electrode active material may include one or more lithium metal oxides represented by Chemical Formula 1 and Chemical Formula 2 below, which can undergo an electrochemical reaction on the positive electrode current collector to reversibly intercalate and deintercalate lithium ions:

[0135] [Chemical Formula 1]

[0136] Li x [Ni y Co z Mn w M 1 v O2

[0137] [Chemical Formula 2]

[0138] LiM 2 p Mn q P r O4

[0139] In Chemical Formula 1 and Chemical Formula 2,

[0140] M 1 is at least one element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.

[0141] x, y, z, w, and v are 1.0 ≤ x ≤ 1.30, 0.5 ≤ y < 1, 0 < z ≤ 0.3, 0 < w ≤ 0.3, and 0 ≤ v ≤ 0.1, respectively, where y + z + w + v = 1.

[0142] M 2 is Ni, Co or Fe, and

[0143] p is 0.05≤p≤1.0,

[0144] q is 2-p, and

[0145] r is 0 or 1.

[0146] The lithium metal oxides represented by the above Chemical Formulas 1 and 2 are materials containing high contents of nickel (Ni) and manganese (Mn), respectively, and when used as positive electrode active materials, they have the advantage of being able to stably supply high-capacity and / or high-voltage electricity compared to commonly used positive electrode active materials (such as lithium iron phosphate (LiFeO4)).

[0147] In this case, the lithium metal oxide represented by Chemical Formula 1 may include LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2、LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2, etc. In addition, the lithium metal oxide represented by Chemical Formula 2 may include LiNi 0.7 Mn 1.3 O4; LiNi 0.5 Mn 1.5 O4; LiNi 0.3 Mn 1.7 O4, etc. The lithium metal oxides represented by Chemical Formula 1 and / or Chemical Formula 2 may be used alone or in combination.

[0148] In addition, the content of the positive electrode active material can be 85 parts by weight or more relative to 100 parts by weight of the positive electrode active layer, and more specifically, its content can be at least 90 parts by weight, at least 93 parts by weight, or at least 95 parts by weight relative to 100 parts by weight of the positive electrode active layer.

[0149] Furthermore, the positive electrode active layer may further contain a conductive material, a binder, other additives, and the like in addition to the positive electrode active material.

[0150] In this case, the conductive material used to improve the electrical properties of the positive electrode can be any material commonly used in the art, but more particularly, can include at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, silk screen black, Ketjen black, Super-P, channel black, furnace black, lamp black, thermal black, graphene and carbon nanotubes.

[0151] In addition, the content of the conductive material may be 0.1 to 5 parts by weight relative to 100 parts by weight of the positive electrode active layer. Specifically, the content of the conductive material may be 0.1 to 4 parts by weight; 2 to 4 parts by weight; 1.5 to 5 parts by weight; 1 to 3 parts by weight; 0.1 to 2 parts by weight; or 0.1 to 1 part by weight relative to 100 parts by weight of the positive electrode active layer.

[0152] In addition, the binder is used to bind the positive active material, the positive electrode additive and the conductive material to each other, and the binder can be used without limitation as long as it has this function. Specifically, the binder may include one or more resins selected from the group consisting of: vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate and copolymers thereof. In one example, the binder may include polyvinylidene fluoride.

[0153] In addition, the content of the binder may be 1 to 10 parts by weight, more specifically 2 to 8 parts by weight; or 1 to 5 parts by weight of each positive electrode active layer.

[0154] The total thickness of the positive electrode active layer is not particularly limited, but may be 50 μm to 300 μm. More specifically, the total thickness of the positive electrode active layer may be 100 μm to 200 μm; 80 μm to 150 μm; 120 μm to 170 μm; 150 μm to 300 μm; 200 μm to 300 μm; or 150 μm to 190 μm.

[0155] In addition, as the positive electrode current collector, the positive electrode can use a positive electrode current collector having high conductivity without causing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. can be used, and in the case of aluminum or stainless steel, aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can also be used. In addition, considering the conductivity and total thickness of the positive electrode to be manufactured, the average thickness of the current collector can be appropriately 3 μm to 500 μm.

[0156] In addition, the separator disposed between the positive electrode and the negative electrode of each unit cell is an insulating film with high ion permeability and mechanical strength, and may include but is not limited to one or more polymers commonly used in the art, such as polypropylene, polyethylene and polyethylene-propylene copolymers, which are chemically resistant and hydrophobic. The separator may be in the form of a porous polymer substrate, such as a sheet or non-woven fabric containing the above polymer, and in some cases may be in the form of a composite separator in which organic or inorganic particles are coated on a porous polymer substrate by an organic binder. In addition, the average pore size of the separator may be 0.01 to 10 μm, and the average thickness may be 5 to 300 μm.

[0157] The lithium secondary battery of the present invention may be a secondary battery including a stacked, folded or folded-stacked electrode assembly without particular limitation. As an example, the lithium secondary battery of the present invention may be a pouch-type secondary battery or a prismatic secondary battery.

[0158] Pouch-type and / or prismatic secondary batteries have an advantage of being highly available in terms of energy density because they can pack high-density secondary battery unit cells within a limited space.

[0159] Negative electrode manufacturing method

[0160] In addition, in one embodiment, the present invention provides a method for manufacturing a negative electrode for a lithium secondary battery, comprising:

[0161] applying a first negative electrode slurry and a second negative electrode slurry such that the first negative electrode slurry is located on at least one surface of the negative electrode current collector and the second negative electrode slurry is located on the first negative electrode slurry;

[0162] applying a magnetic field to the applied first negative electrode slurry and second negative electrode slurry;

[0163] The first negative electrode slurry and the second negative electrode slurry to which the magnetic field is applied are dried to form a negative electrode active layer, wherein:

[0164] The first negative electrode slurry comprises a first carbon-based negative electrode active material,

[0165] The second negative electrode slurry comprises a second carbon-based negative electrode active material and a silicon-based negative electrode active material, wherein:

[0166] The magnetic field is applied at a strength of 10,000 G or less.

[0167] The negative electrode manufacturing method of the present invention refers to a method for manufacturing the negative electrode of the present invention as described above. The negative electrode manufacturing method can produce a negative electrode by applying a negative electrode slurry to a negative electrode current collector, applying a magnetic field to the surface to which the negative electrode slurry is applied, and drying each negative electrode slurry, wherein the crystallization characteristics of the negative electrode active material of the negative electrode active layer are controlled.

[0168] Here, the step of applying the negative electrode slurry includes coating the surface of the moving negative electrode current collector by discharging the negative electrode slurry containing the carbon-based negative electrode active material. The above steps can be applied in any manner commonly used in the art without limitation, but are preferably performed by die coating. The die coating method can be performed by a slit die having a gasket for controlling the discharge conditions of the negative electrode slurry. In this case, by controlling the shape of the gasket, the load amount of the negative electrode slurry applied to the negative electrode current collector, the coating thickness, etc. can be easily controlled.

[0169] In the present invention, a double mold is used to simultaneously apply the first negative electrode slurry and the second negative electrode slurry to the negative electrode current collector. This has the advantage of significantly increasing process efficiency compared to applying each slurry sequentially.

[0170] At the same time, the step of applying a magnetic field to the negative electrode slurry may be a step of controlling the crystal properties of the negative electrode active material contained in the negative electrode slurry. Specifically, the step may include applying a magnetic field to the surfaces of the first negative electrode slurry and the second negative electrode slurry applied to the negative electrode current collector, so that the ab axis crystal plane of the carbon-based negative electrode active material contained in each negative electrode slurry is arranged at a higher angle relative to the negative electrode current collector, and the (1,1,1) crystal plane characteristics of the silicon-based negative electrode active material contained in the second negative electrode slurry are controlled.

[0171] In this case, the application of the magnetic field can be applied by the magnetic components disposed on the upper and lower parts of the negative electrode collector, and the negative electrode collector moves with the negative electrode slurry applied to its surface. In addition, the polarities of the magnetic components on the upper and lower parts can be different.

[0172] In addition, the arrangement value (OI) of the carbon-based negative electrode active material contained in the negative electrode slurry may be controlled by the strength of the applied magnetic field, and the step of applying the magnetic field may be performed under a predetermined magnetic field strength condition.

[0173] Specifically, the step of applying a magnetic field may include applying a magnetic field below 10000G (Gauss), for example 2500G to 9000G; 3000G to 8500G; 3500G to 8500G; 4000G to 8200G; 3600G to 4500G; 4500G to 6500G; 5000G to 7000G; 6000G to 8500G; 7000G to 8500G; or 6000G to 6500G.

[0174] Furthermore, the step of applying a magnetic field may be performed for a duration of 1 to 20 seconds, more specifically 1 to 15 seconds; 1 to 10 seconds; 5 to 20 seconds; 10 to 20 seconds; 11 to 18 seconds; 1 to 5 seconds; 4 to 9 seconds; or 6 to 11 seconds.

[0175] In one example, the step of applying a magnetic field may include applying a magnetic field of 6250±50 G to the negative electrode slurry for 1 second to 5 seconds.

[0176] In addition, as described above, the step of applying the magnetic field can be performed by introducing the magnet components at the upper and lower parts of the applied negative electrode slurry, but the size of the magnet components can be adjusted to be larger than the size of the negative electrode slurry so that the magnetic field applied to the negative electrode slurry can be uniformly applied to the entire surface of the negative electrode slurry. For example, the length ratio of the magnet components based on the length in the width direction of the negative electrode slurry can be 105% to 200%, more specifically, based on the length in the width direction of the negative electrode slurry, the length ratio can be 110% to 180%; 110% to 160%; 110% to 140%; 110% to 130%; 130% to 150%; or 105% to 120%.

[0177] By controlling the magnetic field strength, application time and / or magnet component size as described above in the step of applying the magnetic field, the present invention can satisfy that the arrangement value (OI) of the carbon-based negative electrode active material contained in the second negative electrode slurry is less than 2.5, while satisfying Formula 2 of less than 8.

[0178] In addition, the step of forming the negative electrode active layer may include the steps of drying the negative electrode slurry; and roll-pressing the dried negative electrode slurry.

[0179] In this case, the step of drying the negative electrode slurry may be performed in a manner capable of maintaining the orientation of the carbon-based negative electrode active material contained in the negative electrode active layer without particular limitation.

[0180] For example, the drying step may be performed by applying heat energy to the negative electrode slurry using a hot air dryer, a vacuum oven, or the like to dry the negative electrode slurry.

[0181] In addition, the step of roll-pressing the dried negative electrode slurry is a step of applying pressure to the dried negative electrode slurry to increase the density of the negative electrode active layer using a roll press machine, etc. In this case, the roll press may be performed at a temperature higher than room temperature.

[0182] Specifically, the rolling may be performed at a temperature of 50° C. to 100° C., more specifically at the following temperatures: 60° C. to 100° C.; 75° C. to 100° C.; 85° C. to 100° C.; 50° C. to 90° C.; 60° C. to 80° C. or 65° C. to 90° C. More specifically, the rolling may be performed at a rolling speed of 2 m / s to 7 m / s, or more specifically 2 m / s to 6.5 m / s; 2 m / s to 6 m / s; 2 m / s to 5.5 m / s; 2 m / s to 5 m / s; 2 m / s to 4.5 m / s; 2 m / s to 4 m / s; 2.5 m / s to 4 m / s; 2.5 m / s to 3.5 m / s; 3.5 m / s to 5 m / s; 5 m / s to 7 m / s; 5.5 m / s to 6.5 m / s; or 6 m / s to 7 m / s. In addition, the rolling may be performed under a pressure condition of 50 MPa to 200 MPa, more specifically, under a pressure condition of 50 MPa to 150 MPa; 50 MPa to 100 MPa; 100 MPa to 200 MPa; 150 MPa to 200 MPa; or 80 MPa to 140 MPa.

[0183] By roll-pressing the dried negative electrode slurry under the above temperature, speed and / or pressure conditions, the present invention can increase the energy density of the negative electrode while minimizing the change in the arrangement value of the carbon-based negative electrode active material formed in the negative electrode active layer.

[0184] Hereinafter, the present invention will be described in more detail through Examples and Experimental Examples.

[0185] However, the following Examples and Experimental Examples are illustrative of the present invention, and the present invention is not limited to the following Examples and Experimental Examples.

[0186] Examples 1-5 and Comparative Examples 1-3. Preparation of Negative Electrode for Lithium Secondary Batteries

[0187] As carbon-based negative electrode active materials, natural graphite (average particle size (D 50 ): 18±1μm) and artificial graphite (average particle size (D 50 ): 16±1 μm), and as a silicon-based negative electrode active material, silicon oxide (SiO2) is prepared, and the prepared carbon-based negative electrode active material and silicon-based negative electrode active material are used to prepare a first negative electrode slurry and a second negative electrode slurry.

[0188] Specifically, natural graphite and artificial graphite are mixed in a weight ratio of 3.5 to 4.5:5.5 to 6.5, and carbon black is used as a conductive material, carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) are used as binders to prepare a first carbon-based negative electrode active material. Then, 95 parts by weight of the mixed graphite, 1 part by weight of carbon black, 1.5 parts by weight of carboxymethyl cellulose (CMC) and 2.5 parts by weight of styrene butadiene rubber (SBR) are mixed with water so that the solid content is 50% to prepare a first negative electrode slurry.

[0189] In addition, artificial graphite and silicon oxide (SiO2) were mixed in a weight ratio of 85 to 90:10 to 15, and carbon black was used as a conductive material, carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) were used as binders to prepare a negative electrode active material. Then, 95 parts by weight of the mixed graphite and silicon oxide, 1 part by weight of carbon black, 1.5 parts by weight of carboxymethyl cellulose (CMC) and 2.5 parts by weight of styrene butadiene rubber (SBR) were mixed with water to a solid content of 45% to prepare a second negative electrode slurry.

[0190] After preparing each negative electrode slurry, the first and second negative electrode slurries were simultaneously cast onto a copper thin plate (thickness: 10 μm) using a double die coater under roll-to-roll transfer (transfer speed: 5 m / min).

[0191] A permanent magnet having a length ratio of 110-120% based on the length of the negative electrode slurry in the width direction is placed on the upper part of the applied negative electrode slurry and the lower part of the negative electrode current collector, and the magnetic field strength is adjusted as shown in Table 1 below, and the magnetic field is applied for 2 to 3 seconds. The negative electrode slurry to which the magnetic field is applied is hot-air dried to form a negative electrode active layer in the form of a first negative electrode active layer and a second negative electrode active layer stacked sequentially on the negative electrode current collector. The formed negative electrode active layer is rolled at a transfer rate of 3m / s at a pressure of 100-150MPa at 50±1°C to prepare a negative electrode for a lithium secondary battery (the average thickness of the first negative electrode active layer and the second negative electrode active layer is 110±5μm, respectively).

[0192] In addition, for each prepared negative electrode, the second negative electrode active layer was subjected to X-ray diffraction spectroscopy (XRD) to measure the spectrum. In this case, the second carbon-based negative electrode active material and the silicon-based negative electrode active material contained in the second negative electrode active layer were each subjected to an X-ray diffraction (XRD) spectral analysis. The measurement conditions of X-ray diffraction (XRD) are as follows:

[0193] -Target: Cu (Kα ray) graphite monochromator

[0194] - Slits: Divergence slit = 1 degree, Receiving slit = 0.1 mm, Scattering slit = 1 degree

[0195] -Measurement area: (1,1,0) plane: 76.5°<2θ<78.5° / (0,0,4) plane: 53.5°<2θ<56.0°.

[0196] Then, ① the area integral of the peaks representing the (0,0,4) and (1,1,0) crystal planes is calculated from the measured spectrum of the second carbon-based negative electrode active material, and the ratio of these areas (I 004 / I 110 ) to obtain the arrangement value (OI) of the mixed graphite in each region. In addition, ② the area integral (I Si ). The calculated values ​​are shown in Table 1 below.

[0197] [Table 1]

[0198] <![CDATA[D of SiO2 50 > Magnetic field strength OI <![CDATA[I Si ]]> <![CDATA[I Si *OI]]> Comparative Example 1 6±1μm - 5.18 1.60 8.34 Comparative Example 2 0.5±0.05μm 6250G 0.81 1.94 1.57 Comparative Example 3 16±1μm 6250G 0.83 1.92 1.59 Example 1 6±1μm 3500G 2.19 2.64 5.79 Example 2 6±1μm 4000G 1.20 2.81 3.37 Example 3 6±1μm 6250G 0.75 3.73 2.80 Example 4 6±1μm 8050G 0.49 4.24 2.07 Example 5 6±1μm 10100G 0.36 4.50 1.62

[0199] Examples 6-10 and Comparative Examples 4-6. Preparation of lithium secondary batteries

[0200] Preparation of LiNi with a particle size of 5 μm 0.7 Co 0.1 Mn 0.1 Al 0.1 O2 was used as a positive electrode active material and mixed with a carbon-based conductive material and polyvinylidene fluoride as a binder in a weight ratio of 94:3:3 in N-methylpyrrolidone (NMP) to form a slurry, which was cast on an aluminum sheet, dried in a vacuum oven at 120°C, and roll-pressed to prepare a positive electrode.

[0201] The lithium secondary battery was assembled by placing a separator including 18 μm polypropylene between the positive electrode obtained above and the negative electrode prepared in Examples 1-5 and Comparative Examples 1-3, respectively, putting it into a battery case, and then injecting the electrolyte composition.

[0202] Here, the types of negative electrodes applied to the respective lithium secondary batteries are shown in Table 2 below.

[0203] [Table 2]

[0204] Type of cathode used Example 6 The negative electrode prepared in Example 1 Example 7 The negative electrode prepared in Example 2 Example 8 The negative electrode prepared in Example 3 Example 9 The negative electrode prepared in Example 4 Example 10 The negative electrode prepared in Example 5 Comparative Example 4 The negative electrode prepared in Comparative Example 1 Comparative Example 5 The negative electrode prepared in Comparative Example 2 Comparative Example 6 The negative electrode prepared in Comparative Example 3

[0205] Experimental example

[0206] In order to evaluate the performance of the negative electrode of the present invention, the lithium secondary batteries prepared in Examples 6-10 and Comparative Examples 4-6 were subjected to the following experiments:

[0207] 1) Evaluate the expansion rate of secondary batteries during charging

[0208] Each of the lithium secondary batteries of the examples and comparative examples was activated by charging them to 4.2 V at a rate of 0.3 C under CC-CV conditions at 25° C. and discharging them to 2.5 V at a rate of 0.3 C under CC conditions. The volume of the activated lithium secondary batteries in the discharged state was then measured using the Archimedean principle.

[0209] Each activated lithium secondary battery was charged to 4.5V at a rate of 2.0C under CC-CV conditions at 25°C, and the volume of the charged lithium secondary battery was measured in the same manner as the previous volume measurement. The volume change rate of each lithium secondary battery was calculated using the following formula 3, and the calculated volume change rate was determined by the expansion rate of the negative electrode of each lithium secondary battery. The results are shown in Table 3 below.

[0210] [Equation 3]

[0211] Volume change rate during charging = [(volume during charging - volume during discharging) / volume during discharging] × 100

[0212] 2) Evaluation of initial charge capacity and high-rate charge / discharge characteristics

[0213] Each of the lithium secondary batteries prepared in Examples 6-10 and Comparative Examples 4-6 was activated by charging to 4.2 V at a rate of 0.3 C under CC-CV conditions at 25° C., and discharging to 2.5 V at a rate of 0.3 C under CC conditions.

[0214] At a temperature of 25°C, each activated lithium secondary battery was subjected to constant current / constant voltage charging (CC / CV charging), and the initial charge capacity was measured. The battery was charged at a constant current with a current rate of 0.1C until the voltage reached 4.2V, and then cut off at a current rate of 0.005C in a constant voltage mode to maintain 4.2V. In addition, each charged secondary battery was subjected to constant current discharge (CC discharge) and the initial discharge capacity was measured. The constant current discharge was performed at a rate of 1.0C until 1.5V was reached.

[0215] Then, at 25°C, each lithium secondary battery was fully charged to a charge termination voltage of 4.2 to 4.25V with a charging current of 2.0C rate, and the charging capacity was measured. According to the measured charging capacity, the relative charging capacity ratio relative to the initial charging capacity was calculated to evaluate the high-rate charging characteristics of each lithium secondary battery. The lithium secondary battery was then discharged at a rate range of 1.0 to 2.0C at 0.2C intervals to measure the discharge capacity. According to the measured discharge capacity, the relative discharge capacity ratio based on the initial discharge capacity of each discharge rate was calculated to evaluate the high-rate discharge characteristics of each lithium secondary battery. The measurement results are shown in Table 3.

[0216] [Table 3]

[0217]

[0218] As shown in Table 3 above, it can be seen that the lithium secondary battery of the present invention has a reduced expansion rate during charging, and has a higher charge and discharge capacity and a high rate charge and discharge efficiency.

[0219] Specifically, the lithium secondary battery of the embodiment has a high charge capacity (over 462 mAh / g) and excellent high rate charge and discharge characteristics (high rate charge and discharge characteristics under 2C rate condition are greater than 90% and greater than 88%, respectively). The lithium secondary battery of the embodiment also shows reduced volume growth during charging, with an expansion rate of less than 40%.

[0220] This shows that the negative electrode of the embodiment includes a double-layer negative electrode active layer, but by controlling the crystal properties of the carbon-based negative electrode active material and the silicon-based negative electrode active material contained in the second negative electrode active layer located on the outermost side so that they satisfy the conditions of Formula 1 and Formula 2, the charging and discharging capacity of the lithium secondary battery is increased, and the high-rate charging and discharging characteristics are improved.

[0221] It can be seen from these results that the negative electrode for lithium secondary batteries of the present invention has a high charge and discharge capacity and excellent high-rate charge and discharge characteristics.

[0222] While the foregoing has been described with reference to preferred embodiments of the present invention, those skilled in the art will appreciate that various modifications and changes may be made to the present invention without departing from the technical scope of the invention described in the appended claims.

[0223] Therefore, the technical scope of the present invention is not limited to the contents disclosed in the detailed description of the specification but should be defined by the claims of the patent.

Claims

1. A negative electrode for a lithium secondary battery, comprising: A negative electrode current collector; A first negative electrode active layer provided on at least one surface of the negative electrode current collector and containing a first carbon-based negative electrode active material; and A second negative electrode active layer provided on the first negative electrode active layer and containing a second carbon-based negative electrode active material and a silicon-based negative electrode active material, wherein The arrangement value (O.I) of the carbon-based negative electrode active material in the second negative electrode active layer is 2.5 or less according to Formula 1 below and satisfies Formula 2 below as 8 or less: [Formula 1] OI=I 004 / I 110 [Formula 2] I Si *OI In Formula 1 and Formula 2, I 004 represents the peak area representing the (0,0,4) crystal plane in the X-ray diffraction (XRD) spectrum measurement of the negative electrode active layer, I 110 represents the peak area representing the (1,1,0) crystal plane in the X-ray diffraction (XRD) spectrum measurement of the negative electrode active layer, I Si It represents the area ratio of the peak representing the (1,1,1) crystal plane of the silicon-based negative electrode active material in the X-ray diffraction (XRD) spectrum analysis of the negative electrode active layer.

2. The negative electrode for a lithium secondary battery according to claim 1, wherein The arrangement value (O.I) of the carbon-based negative electrode active material in the second negative electrode active layer is from 0.1 to 1.

5.

3. The negative electrode for a lithium secondary battery according to claim 1, wherein The second negative electrode active layer satisfies Formula 2 as from 0.7 to 6.

4. The negative electrode for a lithium secondary battery according to claim 1, wherein The first carbon-based negative electrode active material and the second carbon-based negative electrode active material each contain at least one of natural graphite and artificial graphite.

5. The negative electrode for a lithium secondary battery according to claim 1, wherein The silicon-based negative electrode active material includes silicon (Si), silicon carbide (SiC) and silicon oxide SiO q At least one of the following, wherein 0.8≤q≤2.

5.

6. The negative electrode for a lithium secondary battery according to claim 1, wherein The content of the silicon-based negative electrode active material is from 1% by weight to 40% by weight based on the total weight of the negative electrode active materials contained in the first negative electrode active layer and the second negative electrode active layer.

7. The negative electrode for a lithium secondary battery according to claim 1, wherein The average particle diameter (Dc) of the second carbon-based negative electrode active material is from 1 μm to 50 μm; The average particle diameter (Ds) of the silicon-based negative electrode active material is from 0.1 μm to 10 μm, wherein The ratio of the average particle diameter of the second carbon-based negative electrode active material to the silicon-based negative electrode active material (Dc / Ds) is from 2 to 10.

8. A method for manufacturing a negative electrode for a lithium secondary battery, comprising: Applying a first negative electrode paste and a second negative electrode paste such that the first negative electrode paste is on at least one surface of the negative electrode current collector and the second negative electrode paste is on the first negative electrode paste; Applying a magnetic field to the applied first negative electrode paste and second negative electrode paste; and Drying the applied first negative electrode paste and second negative electrode paste applied with the magnetic field to form a negative electrode active layer, wherein The first negative electrode paste contains a first carbon-based negative electrode active material, The second negative electrode paste contains a second carbon-based negative electrode active material and a silicon-based negative electrode active material, wherein the magnetic field is applied at a strength of 10,000 G or less.

9. The method for producing a negative electrode for a lithium secondary battery according to claim 8, wherein: The step of applying the magnetic field is performed for a duration of from 1 second to 20 seconds.

10. A lithium secondary battery comprising an electrode assembly, the electrode assembly comprising a positive electrode, the negative electrode according to claim 1, and a separator provided between the positive electrode and the negative electrode.

11. The lithium secondary battery according to claim 10, wherein: The positive electrode contains a positive electrode active layer, the positive electrode active layer contains one or more positive electrode active materials of lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2, and is provided on at least one surface of a positive electrode current collector, [Chemical Formula 1] Li x [Ni y Co z Mr w M 1 v ]O2 [Chemical Formula 2] LiM 2 p Mn 1-p O4 In Chemical Formula 1 and Chemical Formula 2, M 1 is at least one element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, x, y, z, w, and v are respectively 1.0 ≤ x ≤ 1.30, 0.5 ≤ y < 1, 0 < z ≤ 0.3, 0 < w ≤ 0.3, and 0 ≤ v ≤ 0.1, where y + z + w + v = 1, M 2 is Ni, Co or Fe, and p is 0.05 ≤ p ≤ 1.

0.

12. The lithium secondary battery according to claim 11, wherein The positive electrode active material includes one or more of the following: LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2、LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2、LiNi 0.7 Mn 1.3 O4、LiNi 0.5 Mn 1.5 O4 and LiNi 0.3 Mn 1.7 O4.

13. The lithium secondary battery according to claim 10, wherein: The electrode assembly is a stacked electrode assembly; a folded electrode assembly; or a fold-stacked electrode assembly.

Citation Information

Patent Citations

  • Gel composition for film-forming sanitizer

    KR1020230076642A